2021
DOI: 10.1111/sed.12885
|View full text |Cite
|
Sign up to set email alerts
|

Detecting initial aragonite and calcite variations in limestone–marl alternations

Abstract: Limestone-marl alternations are commonly used for high-resolution cyclostratigraphic studies and palaeoenvironmental reconstructions, but diagenetic studies indicate that not all limestone-marl alternations reflect genuine differences in the initial sediment composition driven by environmental changes. Differences in the ratios of diagenetically inert trace elements between limestones and marls indicate changes affecting the terrigenous fraction of the precursor sediment. Contrarily, limestone-marl alternation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…The different TiO2/Al2O3 ratios in limestones, marls, and clays in the studied section point to a primary signal that can be attributed to environmental changes, regardless of subsequent differential diagenesis (Fig. C6, see also Nohl et al, 2021). K 2 O/Al 2 O 3 is interpreted as a chemical weathering signal.…”
Section: Selection and Interpretation Of Elemental Ratio Proxiesmentioning
confidence: 82%
See 2 more Smart Citations
“…The different TiO2/Al2O3 ratios in limestones, marls, and clays in the studied section point to a primary signal that can be attributed to environmental changes, regardless of subsequent differential diagenesis (Fig. C6, see also Nohl et al, 2021). K 2 O/Al 2 O 3 is interpreted as a chemical weathering signal.…”
Section: Selection and Interpretation Of Elemental Ratio Proxiesmentioning
confidence: 82%
“…Furthermore, by using a ratio of detrital elements such as TiO 2 /Al 2 O 3, we avoid tracking distortions that arose from early differential diagenesis (Munnecke and Samtleben, 1996). Detrital elements bound to clay minerals are not mobilised during early diagenetic carbonate dissolution and reprecipitation (Nohl et al, 2021). By using a ratio, changes due to enrichment or dilution as a result of this carbonate dissolution and reprecipitation are accounted for (Westphal et al, 2010;Nohl et al, 2021).…”
Section: Selection and Interpretation Of Elemental Ratio Proxiesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the boundary between both lithologies crosscuts obliquely the time lines, thus merging diachronous deposits into one single limestone or marl layer, a phenomenon previously indicated by Nohl & Munnecke (2019) in the Silurian rhythmic series of Sweden (See also : Biernacka et al, 2005;Gani, 2017;Nohl et al, 2021).…”
Section: Diagenetic Aspectsmentioning
confidence: 87%
“…Although some studies suggested a diagenetic origin for these limestone-marls cycles (e.g. Munnecke et al 2001;Nohl et al 2021), the dominant hypothesis is that these alternations result from primary rhythmic sedimentation patterns driven by the so-called "orbital" climatic cycles (Gilbert 1895;Milankovitch 1941). This climatic variability is driven by the sinusoidal fluctuations of the Earth's orbital parameters around the Sun, that control the climate through the seasonal repartition of insolation (e.g.…”
mentioning
confidence: 99%